2009
DOI: 10.1016/s0210-4806(09)72901-8
|View full text |Cite
|
Sign up to set email alerts
|

Uso de alfuzosina para la expulsión de cálculos del tercio distal del uréter

Abstract: Use of alpha-adrenergic blockers for ureteral distal third stones has been shown to be effective for increasing the stone expulsion rate and even the number of stones passed, and for faster symptom relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…There were no significant difference in terms of mean stone size between the Alfuzosin-treated patients and the control study patients (5.94 vs. 5.94mm, respectively) as well as between the Alfuzosin-treated and Tamsulosin-treated groups (5.98 vs. 5.61mm, respectively). The methodological quality of the included studies was quite high for six of the RTCs (Jadad scale: 4–5 of 5 points)[ 11 , 12 , 13 , 15 , 16 , 17 ] and medium quality for three (Jadad scale: 2–3 of 5 points)[ 14 , 18 , 19 ]. The quality of evidence was considered to be moderate according to the GRADE system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant difference in terms of mean stone size between the Alfuzosin-treated patients and the control study patients (5.94 vs. 5.94mm, respectively) as well as between the Alfuzosin-treated and Tamsulosin-treated groups (5.98 vs. 5.61mm, respectively). The methodological quality of the included studies was quite high for six of the RTCs (Jadad scale: 4–5 of 5 points)[ 11 , 12 , 13 , 15 , 16 , 17 ] and medium quality for three (Jadad scale: 2–3 of 5 points)[ 14 , 18 , 19 ]. The quality of evidence was considered to be moderate according to the GRADE system.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of evidence was considered to be moderate according to the GRADE system. Two studies[ 11 , 18 ] reported the stones located in either the upper or lower ureter; the other seven studies[ 12 , 13 , 14 , 15 , 16 , 17 , 19 ] restricted to stones in the distal ureter. All except one trial[ 15 ] reported the additional medication administered for pain relief.…”
Section: Resultsmentioning
confidence: 99%
“…García Morú a et al 7 realizaron un ensayo clínico con 30 pacientes con litiasis en el tercio distal del uré ter, que fueron aleatorizados a recibir bromuro de hioscina o alfuzosina. El grupo de alfuzosina presentó un tiempo de expulsió n má s corto que el grupo control, así como tambié n menor duració n del dolor y mayor tasa de expulsió n del cá lculo (88 frente a 40%).…”
Section: Discusió Nunclassified
“…On the other hand, waiting for stone removal can cause unwanted side effects such as kidney failure and urosepsis. 9,10 Therefore, it is necessary to select the right patient for proper management of ureteric stones. A biomarker that can predict which group of patients with ureteral stones will pass their stone spontaneously and which group is likely to require intervention, to guide the management of patients who are clinically stable at presentation, it is beneficial.…”
Section: Introductionmentioning
confidence: 99%